Intramuscular Migration of Venous Catheter as a Rare Complication of Ventriculoatrial Shunt: Case Report and Literature Review - Hung, Cheng-Che; Chuang, Hao-Yu; Lin, Hung-Lin; Chu, Yen-Tse; Cheng, Cheng Hsin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2017)
The most common procedure to manage hydrocephalus is a ventriculoperitoneal shunt. Other alternatives include a ventriculoatrial (VA) shunt, ventriculopleural shunt, lumboperitoneal shunt, or ventriculocisternal shunt. The VA shunt is a relatively rare procedure for hydrocephalus. As reported, several complications of VA shunt include obstructions, malposition, shunt infections, endocarditis, heart failure, tricuspid regurgitation, intra-atrial thrombus, and pulmonary hypertension. In this case report and literature review, we discuss a rare case of intramuscular migration of a venous tube 1 year after VA shunt implantation. We also report all the possible locations of migration after placement of VA shunt.
Keywords: ventriculoatrial shunt; shunt migration; hydrocephalus